Structural Equation Modelling in Microscoping Nepalese Commercial Banks’ Profit Maximization by Risk Minimization - Khadka, Chakra Bahadur (Economic Journal of Development Issues, 2019)
This paper examines the degree to which the commercial banks of Nepal used risk management practices and techniques in dealing with different types of risk. The structural equation modeling (SEM) is applied in this study to analyze profit maximization and risk minimization of commercial banks in Nepal. Symmetry and balance to cover four aspects and four components of risk management and use of quantitative data from Banking and Financial Statistics of NRB is considered in the study. SEM is the cross-sectional statistical modeling. Factor analysis, path analysis and regression equation SLs are used for data analysis. Maximum likelihood estimation is the additional estimation equation. The significant findings of the study are: important types of risk being faced by the commercial banks of Nepal like credit risk, operational risk, and interest rate risk. Study also finds that the Nepalese commercial banks staff members properly understand risk and its management. Most of the components of risk management are very sound. There is a strong, positive relationship between risk management practices and understanding of risk and its management, board and senior management oversight, risk assessment and measurement, ownership structure and presence of separate risk manager. Findings of the paper are limited to the RMPs of commercial banks of Nepal. Results help to understand the current practices of Commercial Banks of Nepal. Findings can be used as a valuable feedback on improvement to RMPs and will be of significance to those who are interested in the banking sector of Nepal.